Understanding the experiences of seronegative partners in HIV discordant couples - Naran, Sanjay (My University, 2008)
Abstract Introduction HIV serodiscordant couples are presenting more often to their doctors as the epidemic continues to spread. There have been various theories as to why some couples remain discordant, but none have yielded a conclusive answer as yet. The negative partners in discordant couples have previously been ignored. However, more of them are now presenting with psychosocial problems of their own. They are increasingly being recognized as ‘hidden’ patients and as potential resources. The researcher would like to discover what issues and problems these negative partners have so that we can understand and help them. Aims To explore seronegative partners’ experiences and emotions in HIV discordant couples. Methodology Using qualitative interview methods to explore the range of emotions and experiences that seronegative partners in discordant relationships experience at the time of disclosure of the different results and thereafter. Results Three main themes emerged from the research. These were: 1) Emotional problems-These were further sub-divided into expected responses and unexpected responses, based on the researchers own views and from literature reviews.2) Coping strategies- these were further sub-divided into positive and negative coping strategies based on the beneficial or harmful effects on the individual, family or the relationship as well as the increase in risk behaviour associated with each action. 3) Future plans-these were according to the participants and included what they wanted for their future. Conclusion Negative partners in discordant couples have been ignored for too long. They face many challenges and problems but they can also assist in the management of their partners. This was explored in more detail. From the research, a host or experiences and reactions were noted and based on these, recommendations for doctors were drawn up. The recommendations include the following: 1. Doctors should not ignore the negative partner in discordant couples. They are also patients and in need of help and support. They can in turn help the doctor in future treatment of the positive partner. By just acknowledging them and that they are also going through difficult times, allows them to bring out their problems and assist in future management. 2. Always discuss the possibility of discordant results before testing a couple. This possibility can be a source of immense stress and confusion to the couple if they have not been alerted to the fact that it can occur. 3. Both partners in the discordant couple must be screened for depression as there is a high rate of this illness in both groups. Too often, this depression is not actively looked for in the negative partner. Doctor’s who fail to do this, will be neglecting the wellbeing of the family unit. 4. All discordant couples should be offered ongoing counseling sessions, either separately or together as a couple. This will give the often ignored negative partner an opportunity to air their views and problems, not only to the doctor, but if they participate in the sessions as a couple, they may be able to speak to their partners, indirectly, by speaking to the doctor. 5. When faced with a discordant couple, the topic of future parenthood should be raised by the doctor. If this is ignored, it may force some couples to engage in high risk behaviour without them knowing the repercussions of it. The doctor must present all the options available to the couple, including adoption and assisted reproductive techniques as well as the role of antiretroviral medication. 6. Doctors must keep abreast of the latest developments in HIV and treatment as patients expect them to provide answers. This would include the doctor improving his/her computer skills as well as learning and practicing the art of critical reading so that he/she can access valid information for patients when the need arises. 7. Doctors must pay attention to the setup at their surgeries so that they always ensure privacy and confidentiality. This includes the position of the waiting room in relation to the consulting rooms so that what is discussed cannot be heard by others. The doctor must also not leave patient records where subsequent patients can see them. Lastly, the doctor must ensure that his staff members, who do see patient records, are informed of their obligations to patient confidentiality. 8. Doctors should avoid using the term undetectable when reporting on the positive partner’s viral load. This term may be misunderstood by both partners to mean that the virus was no longer present and thus safe sex practices were on longer needed. A better word to use would be “further reduced” or “ in the acceptable range showing good compliance”.
Keywords: seronegative partners; HIV